The protective effect of traditional Chinese medicine Jinteng Qingbi granules on rats with rheumatoid arthritis - Wan, Yingying; Sun, Wenting; Yang, Jiaxi; Wang, Haonan; Wang, Wenqian; Ye, Wanting; Cheng, Guoliang; Li, Bing; Ren, Jianxun; Kou, Qiuai (Frontiers in Pharmacology, 2024)
Introduction: Jinteng Qingbi granules (JTQBG), a traditional Chinese medicine formulation, are widely used for the treatment of rheumatoid arthritis (RA) due to their satisfactory therapeutic efficacy. However, the underlying mechanism of action remains unclear. This study aims to investigate the protective effects of JTQBG against RA and elucidates its potential molecular mechanisms. Methods: A collagen-induced arthritis (CIA) rat model was utilized, and JTQBG (1.25, 2.5, 5 g/kg/day) or methotrexate (MTX, 1 mg/kg/week) was orally administered. The rats’ weight, arthritis index (AI), and paw volume were measured weekly. Synovial hyperplasia of the joints was detected using a small animal ultrasound imaging system. Joint destruction was assessed using an X-ray imaging system. Histopathological examinations were performed using hematoxylin-eosin (H&E), Saffron-O and fast green staining. Serum inflammatory cytokines were detected using ELISA. Furthermore, 4D label-free quantitative proteomics of synovial tissues and non-targeted metabolomics of blood serum were conducted to analyze the molecular mechanisms. Results: JTQBG exerted a significant therapeutic effect on CIA rats by reducing inflammatory cell infiltration, synovial hyperplasia, cartilage erosion, and bone destruction. It also decreased the spleen index, inhibited hyperplasia of the white pulp, and decreased the serum levels of IL-1β and IL-18. Proteomics analysis identified 367 differentially expressed proteins (DEPs) between the Model and Normal groups, and 71 DEPs between the JTQBG and Model groups. These DEPs were significantly enriched in the NF-κB pathway. 11 DEPs were significantly reversed after treatment with JTQBG. Western blot results further validated the expression levels of Nfkb1, Pdk1, and Pecam1, and analyzed the expression levels of p-IKK, p-IκBα, and IκBα. The therapeutic efficacy of JTQBG was partly attributed to the suppression of the NF-κB pathway in synovial tissues. Serum metabolomics identified 17 potential biomarkers for JTQBG treatment of CIA rats, which were closely related to Alanine, aspartate and glutamate metabolism, Tryptophan metabolism, Ascorbate and aldarate metabolism, Arginine metabolism, and Inositol phosphate metabolism. Conclusion: Our findings demonstrated that JTQBG was effective against RA by alleviating synovial inflammation, synovial hyperplasia, and joint destruction. The anti-RA properties of JTQBG were likely attributed to the inhibition of the NF-κB pathway and the regulation of serum metabolite disorders.